ETNOBOTANI MASYARAKAT SAMAWA PULAU SUMBAWA - Mulyati Rahayu; Himmah Rustiami (Scripta Biologica, 2017)
We have conducted an ethnobotany research in Batudulang Village of Batulanteh Subdistrict, Sumbawa Island, West Nusa Tenggara. This study was a direct observation method and data were collected by interview. This study aimed to determine the interaction of local community and its environment and to determine the local knowledge of useful plants. We recorded the people of Samawa utilized 147 plants, 39 were edible plants, 74 were medicinal including cosmetics plants, 12 were sources for building materials and handicrafts, and the rest of 22 were honeybee feed plants, firewood, and ritual plants. This study also revealed that the Samawa community has a local wisdom in the importance of sustainable used of the forest as a habitat for wild honeybees.